Peranan guru bimbingan dan konseling pada kenakalan remaja masa kini dalam filsafat sains modern - Chofsoh, Zannuba Ariffah (Maliki Interdisciplinary Journal, 2024)
Juvenile delinquency which is currently rampant in society can disturb the comfort of the surrounding environment and has the potential to cause dangerous criminal acts. The causes are often related to individual and environmental problems, including the school environment. Adolescence is an important phase in the formation of identity, and deviant behavior among teenagers is a behavior that is mostly a part of broader social problems. Handling juvenile delinquency requires special attention, including approaches that involve increasing self-esteem and the role of guidance and counseling (BK) teachers in schools. Guidance teachers play an important role as counselors, helping students face challenges, providing psychological guidance, and building positive relationships that support students' personal and academic development. The role of guidance and counseling teachers is not only important for students, but also provides benefits for schools, teachers, parents and the wider community.